CHANGES THAT OCCUR IN THE ORGANISM OF YOUNG PLAYERS UNDER THE INFLUENCE OF AGE CHARACTERISTICS AND THEIR PHYSICAL FITNESS - Hamroqulov Rasul; Nishanov Shuhrat (Journals Park Publishing, 2022)
In this article Information is provided about the age characteristics of young players and the changes that occur in their organism under the influence of their physical fitness
Keywords: sport, experiment, young sportsmen.